Enhancing Kindergarten Teachers' Pedagogical Competence through the Academic Qualification Fulfillment Program (PKA): Integrating Institutional Support, Digital Literacy, and Andragogical Learning - Nila Fitria; Fidesrinur; Zahrina Amelia (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The Academic Qualification Fulfillment Program (PKA) is a strategic initiative designed to upgrade the academic qualifications of kindergarten teachers while strengthening their professional competence. However, empirical evidence explaining how institutional support, digital literacy, and andragogical learning collectively contribute to pedagogical competence remains limited. This study examined how the PKA enhances kindergarten teachers' pedagogical competence by integrating these three dimensions within a unified analytical framework. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 140 kindergarten teachers through structured questionnaires and analyzed using descriptive statistics and multiple regression analysis. The quantitative findings were subsequently elaborated through semi-structured interviews with 20 teachers and focus group discussions involving LPTK lecturers and program administrators, with qualitative data analyzed using thematic analysis. The findings demonstrate that the PKA substantially improves teachers' pedagogical competence through the complementary interaction of institutional support, digital literacy, and andragogical learning. Academic mentoring provided by LPTK strengthened instructional capability, while digital literacy facilitated continuous professional learning and the application of innovative teaching practices. Learning activities grounded in andragogical principles further promoted reflective, self-directed, and experience-based professional development. The study contributes to teacher professional development literature by integrating institutional, technological, and adult-learning perspectives into a comprehensive model of pedagogical competence enhancement. These findings provide practical guidance for policymakers and teacher education institutions seeking to improve the effectiveness and sustainability of teacher qualification programs.